2017
DOI: 10.1007/s13187-017-1257-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of HPV-Related Oral Cancer by Dentists: Assessing the Opinion of Dutch Dental Students

Abstract: The aim of this study is to assess dental students' opinions of the dentists' role in primary prevention of human papillomavirus (HPV)-related oral cancer using a crosssectional web-based survey. A questionnaire, containing questions about knowledge of HPV and oral cancer, confidence in head and neck examination and role of the dentist in preventing HPV-related oral cancer, was sent to all students of the Academic Centre of Dentistry Amsterdam (n = 912). One hundred and twenty-six (n = 126) students completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 36 publications
4
44
0
4
Order By: Relevance
“…The above researchers assessed awareness of dental students, whereas the present findings are related to students of various, mainly, nonmedical university courses. [ 21 ] A large need for education related to prophylaxis and prevention of HPV infections, also among students, was emphasized by Stock et al These researchers found that insufficient knowledge of the correlation between HPV infection and oral cancer was presented particularly by students who did not participate in educational interventions. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The above researchers assessed awareness of dental students, whereas the present findings are related to students of various, mainly, nonmedical university courses. [ 21 ] A large need for education related to prophylaxis and prevention of HPV infections, also among students, was emphasized by Stock et al These researchers found that insufficient knowledge of the correlation between HPV infection and oral cancer was presented particularly by students who did not participate in educational interventions. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…Like in the study by Poelman et al the present findings do not show significant differences in the level of awareness related to HPV vaccine, depending on stage of the university course. [ 21 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, researchers have argued that oral health professionals “can take the lead in confronting the HPV- oropharyngeal cancer epidemic” [23] , especially through interprofessional collaboration, such as referring patients to relevant clinicians to receive vaccinations and any needed follow-up care [23] . Interprofessional collaboration highlights some dental providers' acceptance of HPV vaccination efforts, but existing evidence suggests that large numbers of current and future dental providers are not yet ready to discuss HPV vaccines with patients [24] , and dental students have expressed willingness to discuss HPV with patients but still have concerns about information deficits [25] , [26] . Discussing HPV with patients would allow dental providers to engage in primordial prevention efforts—a form of “intervention at the most distal point in the chain of causality” [27] that focuses on preventing risk factors and the social and environmental conditions that lead to disease [28] .…”
Section: Introductionmentioning
confidence: 99%
“…Con base en lo anterior, es cierto que aĂșn en la actualidad existen temas tabĂș difĂ­ciles de abordar, sin embargo, concientizar a nuestros pacientes acerca de la forma de contagio del virus y los riesgos que trae consigo dicha presencia en la cavidad bucal propiciarĂĄ una disminuciĂłn importante en la incidencia de neoplasias malignas originadas por vph. Poelman et al mencionaron una serie de puntos acerca del papel del odontĂłlogo ante dicho virus, en los cuales incluyen la importancia de informar a nuestros pacientes acerca de la presencia del vph, discutir acerca de los pros y contras de la vacunaciĂłn contra el virus, asĂ­ como realizar diagnĂłsticos tempranos de lesiones potencialmente sospechosas [50].…”
Section: Lesiones Potencialmente Cancerizablesunclassified